2017
DOI: 10.1002/chem.201705066
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of Electron‐Transfer Properties of Dicopper‐Bound Reduced Dioxygen Species by a Cryo‐Spectroelectrochemical Approach.

Abstract: Direct experimental determination of redox properties of superoxo (O ) and peroxo (O ) embedded in dicopper complexes bearing an unsymmetrical binucleating ligand was achieved using cryo-electrochemistry and cryo-spectroelectrochemistry in dichloromethane. Cyclic voltammetry for dicopper(I) (1 ) oxidation to a Cu Cu mixed-valent species (1 ) under inert atmosphere at 193 K reveals slow heterogeneous electron-transfer kinetics, indicative of a large reorganization energy. Oxygenation of the dicuprous complex 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…In subsequent work, it was demonstrated that C can be reversibly oxidized at low potential (−0.59 V vs Fc/Fc + ), giving the spectroscopically characterized μ-1,2-superoxo dicopper­(II) complex D (Scheme ) whose H atom abstraction (HAA) thermochemistry could be established . Using a ligand scaffold with a central phenolate bridge, Karlin et al studied a related Cu II 2 (O 2 •– ) complex, which was obtained by reacting the mixed-valent Cu I Cu II precursor with O 2 and was shown to consist of a mixture of μ-1,2 and μ-1,1 superoxo isomers in rapid equilibrium. , A kinetically facile superoxo/peroxo interconversion with low reorganization energy (at E = −0.24 V vs Fc/Fc + ) was revealed, reflecting that the redox process occurs at the O 2 -derived unit. , Most recent work focused on correlations between properties of the supporting ligands and superoxo HAA capabilities, in view of the very different OO-H bond dissociation free energies (BDFEs) of the hydroperoxo products derived from D and one of Karlin’s phenolate-based Cu II 2 (O 2 •– ) complexes (69.4 kcal/mol vs 81.8 kcal/mol). , However, crucial structural characterization of any dicopper superoxo species is lacking so far.…”
Section: Introductionsupporting
confidence: 75%
See 2 more Smart Citations
“…In subsequent work, it was demonstrated that C can be reversibly oxidized at low potential (−0.59 V vs Fc/Fc + ), giving the spectroscopically characterized μ-1,2-superoxo dicopper­(II) complex D (Scheme ) whose H atom abstraction (HAA) thermochemistry could be established . Using a ligand scaffold with a central phenolate bridge, Karlin et al studied a related Cu II 2 (O 2 •– ) complex, which was obtained by reacting the mixed-valent Cu I Cu II precursor with O 2 and was shown to consist of a mixture of μ-1,2 and μ-1,1 superoxo isomers in rapid equilibrium. , A kinetically facile superoxo/peroxo interconversion with low reorganization energy (at E = −0.24 V vs Fc/Fc + ) was revealed, reflecting that the redox process occurs at the O 2 -derived unit. , Most recent work focused on correlations between properties of the supporting ligands and superoxo HAA capabilities, in view of the very different OO-H bond dissociation free energies (BDFEs) of the hydroperoxo products derived from D and one of Karlin’s phenolate-based Cu II 2 (O 2 •– ) complexes (69.4 kcal/mol vs 81.8 kcal/mol). , However, crucial structural characterization of any dicopper superoxo species is lacking so far.…”
Section: Introductionsupporting
confidence: 75%
“…Experimental and computational evidence reveal an S = 1/2 spin ground state for the Cu II –O 2 •– –Cu II core and a negligible energy penalty associated with moderate changes of the Cu–O–O–Cu dihedral angle in both the peroxo and superoxo species. This work provides a structural basis for the previously observed , low reorganization energy of the kinetically facile 1e – interconversion of such superoxo/peroxo dicopper­(II) couples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the irreversible 1e reduction of 3 R is comparable to the monoelectronic and reversible electron-exchange reactions detected for the end-on superoxo/peroxo pyrazolate-and xylO-based complexes (entries 4 and 5). 74,75 Interestingly, the reduction potential of 3 NO 2 (entry 8) is close to that of Kodera's side-on peroxodicopper(II) species (entry 7), although the latter is a 2e process. 76 Overall, using such comparisons to make educated assignments of the electrochemical processes remains tentative given the large variety of ligands, charge, nuclearity, and bonding topology of the reported complexes.…”
mentioning
confidence: 68%
“…395second system (process D) at E D (−1 75. V < E D < −1.21 V),396 which is quasi-reversible or irreversible, depending on R 397 (Figures 4 and S31).…”
mentioning
confidence: 99%